2003
DOI: 10.1097/00003226-200307000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Pigment Epithelium-Derived Factor and Increased Vascular Endothelial Growth Factor Levels in Pterygia

Abstract: Pterygia exhibit significantly lower PEDF but higher VEGF levels than those in normal corneas and conjunctivae. The decreased PEDF level in pterygia may play a role in the formation and progression of pterygia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 16 publications
2
73
1
3
Order By: Relevance
“…We should emphasize that VEGF has been reported 28 to be expressed in normal conjunctivae and other ocular tissues with neoangiogenesis. The result of the presented study contradicts previous reports, [29][30][31][32] which demonstrated higher VEGF expression levels in pterygium compared to normal conjunctiva. We must notice that with the exception of the study of Van Setten et al 32 and Marcovich et al, 29 all other studies focus on the overexpression of VEGF in epithelial and vascular endothelial component of pterygium compared to normal conjunctivae.…”
Section: Discussioncontrasting
confidence: 99%
“…We should emphasize that VEGF has been reported 28 to be expressed in normal conjunctivae and other ocular tissues with neoangiogenesis. The result of the presented study contradicts previous reports, [29][30][31][32] which demonstrated higher VEGF expression levels in pterygium compared to normal conjunctiva. We must notice that with the exception of the study of Van Setten et al 32 and Marcovich et al, 29 all other studies focus on the overexpression of VEGF in epithelial and vascular endothelial component of pterygium compared to normal conjunctivae.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in agreement with previous studies that demonstrated constitutive cytoplasmic VEGF mRNA and protein expression in several epithelia, 35 including the conjunctival epithelium. 36 In addition, VEGF was expressed by vascular endothelium in the conjunctiva from patients with active trachoma. This finding is consistent with previous studies that demonstrated expression of VEGF mRNA and protein in stimulated human vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the pterygium tissue, an abnormal mass of fibrovascular tissue that extends from the conjunctiva onto the cornea, several reports described immunoreactivity for VEGF in the vascular endothelium. 21,36 In addition to VEGF, the vascular endothelium in trachoma expressed the proliferative endothelial marker CD105. The CD105 antibody binds preferentially to the activated endothelial cells that participate in angiogenesis, but expression is weak/or negative in vascular endothelium of normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the increased expression of basic fibroblast growth factor (bFGF), transforming growth factor (TGFβ), vascular endothelial growth factor (VEGF), and plateletderived growth factor correlates with the formation and recurrence of pterygia (811) . Bevacizumab (Avastin®, Genentech, Inc., San Francisco, CA, USA) is a humanized monoclonal antibody to VEGF designed for intravenous (IV) administration and approved for the treatment of colorectal (11) . Various clinical trials have shown that intravitreal admi nistration is well tolerated and associated with an improvement in visual acuity, decrease in central retinal thickness, and decrease in angiographic leakage (12,13) .…”
Section: Introductionmentioning
confidence: 99%